Revitalizing a community library as a strategy for enhancing literacy of Kampung Jati Baru, Tangerang City - Umam, Fuadul (Community Empowerment, 2025)
The lack of facilities and activities supporting literacy poses a significant challenge in many communities, particularly in suburban urban environments. This community service program aimed to revitalize a reading house in Kampung Jati Baru, Benda Village, as a comprehensive strategy to increase reading interest and community participation in literacy activities. The implementation method involved three main stages: observation and community needs mapping; improvement of reading house infrastructure (including a reading park and public restrooms) and environmental greening; and enhancement of book collections followed by joint reading activities and training. The program successfully revitalized the reading house and established supporting facilities, creating a comfortable, child-friendly, and accessible learning space. Evaluation results showed a significant increase in the number of children visiting the reading house, greater parental participation in reading house activities, and increased utilization of the reading house as a community learning and discussion space. This revitalization proved effective in empowering the community through enhanced literacy.